WE3 : the 20th anniversary deluxe edition - Morrison, Grant (DC Comics, 2024)
"Writer Grant Morrison and artist Frank Quitely deliver the emotional journey of WE3 - three house pets weaponized for lethal combat by the government - as they search for "home" and ward off the shadowy agency who created them. Deep inside a top-secret U.S. Air Force research facility, a revolution in cybernetics is taking shape. Using ordinary domestic animals for their test subjects, the scientists of Project AWE have created a new class of cyborgs - flesh-and-metal creatures designed to rule the battlefields of tomorrow. The project's crowning achievement is a trio of prototypes code-named WE3 - each one custom-built and trained to work as specialists within a team. With their nervous systems enhanced and supplemented by cutting-edge military hardware, WE3 are the ultimate smart weapons - programmable yet autonomous, loyal yet utterly ruthless. But successful as they are, WE3 are still only prototypes, to be dismantled when their testing is complete. Inside their fearsome mechanical shells, however, are three lost pets whose amplified traits include the will to survive- an instinct which proves to be even stronger than their makers knew. Faced with destruction, WE3 runs -out into a frightening and confusing world, where they are now as much of a threat as those who hunt them. Relentlessly pursued, WE3 fights with the combined firepower of a battalion - and a faint, warm memory of somewhere called "Home.""--